Construction of Nonmetallic p‐n Heterojunction With Face‐to‐Face Structure for Drastically Enhanced Photocatalytic Performance. Issue 4 (11th February 2019) - Wang, Shuhao; Li, Chunmei; Han, Juan; Wang, Lei; Lu, Zhiyuan; Wu, Jiacong; Wang, Yun
Abstract: It is still a great challenge to exploit high‐efficiency nonmetallic composite photocatalysts by structural design for improving H2 production performance. Here, the nonmetallic p‐n heterojunctions with face‐to‐face structure are prepared via hydrothermal in‐situ polymerization of PEDOT on the surface of g‐C3 N4 . The face‐to‐face modification of PEDOT on g‐C3 N4 not only broadens the response in the visible light region but also increases the electron delocalization of conjugated system, which results in improving the visible light harvest ability and separation efficiency of charge carriers. The obtained PEDOT/g‐C3 N4 heterojunctions display the improved H2 production activity, and the optimal H2 production rate reaches up to 3636.6 μmol g −1 h −1 with QE value of 5.6% at 420 nm, which is 5.46 times higher than that of pure g‐C3 N4 (665.8 μmol g −1 h −1 ). Abstract : A new nonmetallic p‐n heterojunction with face‐to‐face structure was fabricated by p‐type poly(3, 4‐ethylenedioxythiophene) (PEDOT) modifying on the surface of n‐type g‐C3 N4 via a simple hydrothermal in‐situ polymerization strategy, which obviously improves the separation efficiency of charge carriers and broadens the visible light response range.